A Braitenberg Vehicle Based on Memristive Neuromorphic Circuits. (21st January 2020) - Wang, Cong; Yang, Zaizheng; Wang, Shuang; Wang, Pengfei; Wang, Chen-Yu; Pan, Chen; Cheng, Bin; Liang, Shi-Jun; Miao, Feng
Abstract : Autonomous Vehicles A smart autonomous vehicle in which the processing unit is based on a memristive neuromorphic circuit is demonstrated by Cong Wang, Shi‐Jun Liang, Feng Miao, and co‐workers, in article number 1900103 . The vehicle exhibits self‐adaptive behaviors and is capable of learning to avoid obstacles and track the pathway, showing huge potential for future development of autonomous robots with real‐time processing.